2021
DOI: 10.1111/eci.13716
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of crossed cerebellar diaschisis after cerebral infarction in MCAO rats based on DKI

Abstract: Objective: To observe the expression of N-methyl-D-aspartate (NMDA), apoptosis and the effect on neurological function recovery in rat model with middle cerebral artery occlusion (MCAO). Diffusion kurtosis imaging (DKI) was used to evaluate crossed cerebellar diaschisis (CCD) and to provide experimental and theoretical basis for the clinical treatment. Materials and Methods:The MCAO models were established in rats. Eightyfour rats were randomly and evenly divided into 7 groups, including control group, 6-h gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
3
2
0
Order By: Relevance
“…The pattern of HI injury observed by MK, with a sharp increase in the MK value of the lesion region at 12 h post-injury, demonstrates a dramatic change in the degree of injury between 0 and 12 h, indicating rapid progression of hypoxic and ischemic brain cytotoxic edema. This finding is in agreement with the results of Xiao et al ( 2020 ) and Ma et al ( 2022 ), suggesting a continuous deterioration of the lesion. Then, it gradually decreased over 5 days, approaching baseline levels, but it still remained higher than that in the controls.…”
Section: Discussionsupporting
confidence: 94%
“…The pattern of HI injury observed by MK, with a sharp increase in the MK value of the lesion region at 12 h post-injury, demonstrates a dramatic change in the degree of injury between 0 and 12 h, indicating rapid progression of hypoxic and ischemic brain cytotoxic edema. This finding is in agreement with the results of Xiao et al ( 2020 ) and Ma et al ( 2022 ), suggesting a continuous deterioration of the lesion. Then, it gradually decreased over 5 days, approaching baseline levels, but it still remained higher than that in the controls.…”
Section: Discussionsupporting
confidence: 94%
“…The phenomenon of diaschisis was associated with clinical outcomes and was considered a potential indicator of recovery development ( Lin et al, 2009 ). Similarly to the study mentioned above, Ma et al (2022) found significant decreases in cerebellar diffusivity. However, their results differ in the cellular reaction to diaschisis ( Ma et al, 2022 ).…”
Section: The Post-ischemic Response In Specific Structures Of the Rem...supporting
confidence: 79%
“…Similarly to the study mentioned above, Ma et al (2022) found significant decreases in cerebellar diffusivity. However, their results differ in the cellular reaction to diaschisis ( Ma et al, 2022 ). While Yang et al (2013) described healthy-looking neurons with preserved numbers, Ma et al (2022) noticed a high number of apoptotic cells, especially 24 h after ischemia ( Yang et al, 2013 ; Ma et al, 2022 ).…”
Section: The Post-ischemic Response In Specific Structures Of the Rem...supporting
confidence: 79%
See 1 more Smart Citation
“…The development of diffusion kurtosis imaging (DKI) complements routine ADC analysis by including a kurtosis term that reasonably accounts for the non-Gaussian diffusion feature. Indeed, DKI is promising to characterize the tissue heterogeneity following ischemic insult (19)(20)(21)(22)(23). In a transient experimental stroke model, it has been demonstrated that the DWI lesion without kurtosis abnormality is more likely to renormalize after reperfusion.…”
Section: Introductionmentioning
confidence: 99%